2021
DOI: 10.3390/ijerph18115769
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Procedures, Diagnoses, and Treatment Outcomes of Patients with Presumptive Tuberculosis Pleural Effusion in Uzbekistan

Abstract: Tuberculosis (TB) pleural effusion (TPE) is the second most common manifestation of extrapulmonary TB (EPTB), which remains a great diagnostic challenge worldwide. In Uzbekistan, there has been no formal evaluation of the actual practices of diagnosing and treating TPE. Our cohort study therefore aimed to describe the frequency and types of different diagnostic procedures of TPE during 2017–2018 and assess the association of baseline characteristics and establish diagnostic methods with TB treatment outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…In this experiment, 92.8 percent of the total sputum samples showed positive results for pulmonary tuberculosis on a smear test; the fact that it poses a danger of infecting others by droplet or airborne transmission 16,17 is one reason why it could be considered a source of community contagiousness. In addition, the findings demonstrated that patients with EPTB were more likely to have pleural infections than any other type of infection, which is consistent with (9,18) in Iraq and (19,20) in Iran and Uzbekistan; further research has found that lymph nodes are to blame for nearly half of the cases of extra-pulmonary tuberculosis (EPTB) in Iraqi Kurdistan 21 and in Turkey 22 . For instance, the genitourinary system and the skin were the two most common sites of infection in Hong Kong 23 , but in the United States, bone and joint infections were more prevalent 24 .…”
Section: Discussionsupporting
confidence: 65%
“…In this experiment, 92.8 percent of the total sputum samples showed positive results for pulmonary tuberculosis on a smear test; the fact that it poses a danger of infecting others by droplet or airborne transmission 16,17 is one reason why it could be considered a source of community contagiousness. In addition, the findings demonstrated that patients with EPTB were more likely to have pleural infections than any other type of infection, which is consistent with (9,18) in Iraq and (19,20) in Iran and Uzbekistan; further research has found that lymph nodes are to blame for nearly half of the cases of extra-pulmonary tuberculosis (EPTB) in Iraqi Kurdistan 21 and in Turkey 22 . For instance, the genitourinary system and the skin were the two most common sites of infection in Hong Kong 23 , but in the United States, bone and joint infections were more prevalent 24 .…”
Section: Discussionsupporting
confidence: 65%